Evolution and recent progress of Computed Tomography Scan (CT- Scan) - yosafat valdino; jonannes a. pradana; niken t. listyorini (Liaison Journal of Engineering, 2023)
The CT Scan (Computed Tomography) has been an integral instrument for the medical field to observe and diagnose patients. Throughout time, the CT scan has been developed over generations; from the first and up to the seventh generation. These developments were to ensure a shorter duration of scan-time (from 25 minutes down to a matter of a few seconds), higher resolution of imaging with low levels of noise, simple and quick to calibrate, and reduce the radiation dosage on the patients. One key development of the CT scan is the invention of multi-slice. This generates clearer images with better resolution compared to the previous generations. The CT scan is still developing as a technology, and looking towards the future, more compact designs of the CT scanner are being developed and the design is being streamlined to allow automation of the process. Keywords: CT Scan; Report; Liaison Journal of Engineering; International University Liaison Indonesia